Ukuran Perusahaan, Liability, Leverage, Profitabilitas, terhadap Nilai Perusahaan pada Perusahaan Industri Dasar dan Kimia - Unjuk br. Ginting; Nina Purnasari; Mega Utami Tambunan (IPM2KPE, 2022)
This study aims to determine the significance of the effect of firm size, liability, leverage, profitability on firm value in the basic and chemical industries on the Indonesia Stock Exchange 2017-2020, with a population of 43 companies. This research method is descriptive quantitative. Determination of the number of samples in this study using purposive sampling method. The analysis technique in this research is multiple linear regression using SPSS as data processing. The results showed that firm size had a positive effect on firm value, liability had a positive effect on firm value, leverage had a positive effect on firm value, and profitability had a positive effect on firm value. In conclusion, the variables of firm size, liability, leverage and profitability simultaneously have a significant effect on firm value in Basic and Chemical Industrial Companies listed on the Indonesia Stock Exchange in 2017-2020. Keywords: Leverage, Liability, Firm Value, Profitability, Firm Size